The objective assessment of striking force in combat sports using sport-specific measurement devices - a review - Akbas, A.; Brachman, A.; Gzik, B.; Bacik, B. (Archives of Budo, 2021)
Background and Study Aim: Throughout the literature, numerous measurement systems have been designed aiming to provide a point of reference to scale the intrinsic performance of combat sports athletes. However, magnitude of force exerted by the athletes variedgreatly between studies and it is difficult to find consistencies in research in this area. Thus, the purpose of this study was to review recent research regarding the striking (punching and kicking) forces and usefulness of sport-specific measurement devices exclusively dedicated for combat sports athletes.